Internalized weight stigma in women with class III obesity: A randomized controlled trial of a virtual lifestyle modification intervention followed by a mindful self‐compassion intervention. (11th June 2022) - Braun, Tosca D.; Olson, Kayloni; Panza, Emily; Lillis, Jason; Schumacher, Leah; Abrantes, Ana M.; Kunicki, Zachary; Unick, Jessica L.
Abstract: Background: Internalized weight stigma (Internalized‐WS) is prevalent among individuals with severe obesity, particularly women, and is associated with shame, disordered eating, and weight gain. Effective, accessible interventions that address both severe (Class‐III) obesity and Internalized‐WS are needed. This randomized pilot trial evaluated the feasibility, acceptability, and preliminary efficacy of a fully‐remote lifestyle modification intervention (LM) followed by mindful self‐compassion training (MSC) or control. Methods: Twenty‐eight women with Class‐III obesity (46.6 ± 3.7 kg/m 2 ) and elevated Internalized‐WS were randomized to a virtually‐delivered 4‐month LM followed by a 2‐month MSC or cooking/dietary education (CON). Psychosocial measures/weight were assessed at baseline, 4‐(post‐LM), 6‐(post‐MSC/CON), and 9‐month (follow‐up). Results: Improvements in Internalized‐WS, shame, and self‐compassion were observed with LM. Mean 4‐month weight loss was 6.3 ± 3.7%. MSC had lower attendance and usefulness ratings versus CON. Post‐MSC/CON, MSC yielded significant and/or meaningful improvements in Internalized‐WS, self‐compassion, and intuitive eating relative to CON. Weight loss did not differ by group at 6‐month, and at 9‐month trended lower in MSC versus CON. Conclusion: Virtual LM is feasible, acceptable, and leads to significant weight loss among women with severe obesity; MSC led to further improved Internalized‐WS, self‐compassion, and intuitive eating. Continued work is needed to elucidate effects of self‐compassion training on Internalized‐WS, its mechanisms, and linkages to cardiometabolic health and long‐term weight loss.